Understanding barriers and enablers of tuberculosis prevention in high-risk boarding school settings - Bella Wiranti; Arih Diyaning Intiasari; Dwi Sarwani Sri Rejeki (Science Midwifery, 2026)
Tuberculosis prevention remains a significant challenge in high-risk boarding school settings due to overcrowding, prolonged close contact, and limited institutional health governance. At the same time, existing Research has largely emphasised epidemiological and individual-level factors with limited attention to contextual and institutional dynamics, particularly among adolescents in congregate educational environments. This qualitative exploratory study aimed to examine barriers and enablers to tuberculosis prevention from the perspectives of adolescents, caregivers, school administrators, and health professionals, using in-depth interviews and focus group discussions with purposively selected participants involved in boarding school health management and tuberculosis prevention. Thematic analysis revealed that the availability of basic environmental facilities, caregiving support, and strong institutional cohesion served as key enablers of tuberculosis prevention; however, these were constrained by overcrowded living conditions, the absence of formal tuberculosis-specific procedures, tuberculosis-related stigma among adolescents, limited financial and health system support, informal governance practices, and fear of social consequences, which collectively hindered early reporting and preventive behaviors. Overall, tuberculosis prevention in boarding schools is shaped by a complex interplay of environmental, institutional, and sociocultural factors, underscoring the need for context-sensitive, institution-based prevention strategies that address stigma, strengthen governance, and enhance collaboration with health systems to reduce tuberculosis risk among adolescents in boarding schools.